The SPAC-bubble: The initial performance of SPACs compared to traditional IPOs - Aatola, Lari (My University, 2023)
Recently, the IPO market has been very active in the U.S. Especially the years 2020 and 2021 saw a high volume of new listings. At roughly the same time, Special Purpose Acquisition Companies (“SPACs”) gained popularity as an alternative to traditional IPOs. The record number of SPACs was recorded in 2021. The primary purpose of this study is to analyze the reasons for the recent appearance and popularity of SPACs. One way this is achieved is by examining the initial returns of SPACs, and then comparing those to IPOs. The intended contribution of this study is to compare the SPACs and IPOs and the initial returns. The performance of SPACs has been previously studied in previous research. However, the focus has mainly been on the performance of SPAC after the acquisition. The purpose of this study is to focus on the initial performance after the listing. The initial performance of SPACs and IPOs is examined using an event study methodology. The data sample consisted of 318 SPACs and 461 IPOs. Alone or compared to IPOs, the findings suggest that SPACs do not generate positive excess returns. However, the finding is made that the distribution of returns for SPACs and IPOs is significantly different. Considering the distribution of SPAC returns and IPO returns are noticeable different samples.

Listautumismarkkinat ovat viime aikoina olleet erittäin aktiivisia Yhdysvalloissa. Erityisesti vuosina 2020 ja 2021 uusia listauksia on nähty runsaasti. Suunnilleen samaan aikaan Special Purpose Acquisition Companies ("SPAC") nousi suosioon, vaihtoehtona perinteisille listautumisajoille. Ennätysmäärä SPAC:eja nähtiin vuonna 2021. Tämän tutkimuksen ensisijainen tarkoitus on analysoida SPAC:ien viimeaikaisen suosion syitä. Yksi tapa saavuttaa tämä on tutkia SPAC:ien tuottoja ja vertaamalla niitä perinteisiin listautumisiin. Tämän tutkimuksen tarkoituksena on verrata SPAC:ien ja perinteisten listautumisien tuottoja. SPAC:ien suorituskykyä on tutkittu aiemminkin lukuisissa tutkimuksissa. Painopiste näissä aikaisemmissa tutkimuksissa on kuitenkin ollut lähinnä SPAC:n tuotot yrityskaupan jälkeen. Tämän tutkimuksen tarkoituksena on keskittyä tuottoihin heti listautumisen jälkeen. SPAC:ien ja perinteisten listautumisien tuottoja tarkastellaan tapahtumatutkimusmetodologialla. Data kostuu 318 SPAC:sta ja 461 IPO:sta. Yksin SPAC:ien tuottoja tai listautumisiin verrattuna, havainnot viittaavat siihen, että SPAC:it eivät tuota positiivista tuottoa. Tästä huolimatta, voidaan tehdä havainto, että SPAC- ja IPO-tuottojen jakautuminen on hyvin erilaista.
Keywords: fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance